Monetary policy strategies in the Asia and Pacific Region: What way forward? - Andrew Filardo; Hans Genberg (Asian Development Bank Institute (ADBI), 2010)
Monetary policy frameworks in the Asia and Pacific region have performed well in the past decade as judged by inflation outcomes. We argue that this is due to three principal factors: (i) central banks have focused on price stability as the primary objective of monetary policy, (ii) institutional setups have been put in place that are supportive of the central banks' abilities to carry out their objectives, and (iii) economic policies in general have been supportive of the pursuit of price stability, in particular the adoption of prudent fiscal policies that have reduced concerns of fiscal dominance. The financial systems in the region have also held up well in the face of the current crisis, notwithstanding more adverse liquidity conditions in several markets and pressures on certain exchange rates that spilled over from the West. It may nevertheless be useful to ask whether changes in monetary policy frameworks should be contemplated. This paper concludes that: (i) for economies with well developed financial markets, there may be little value in using unconventional monetary policies in the absence of financial crises, because in normal times such policies are not likely to be effective and may further reduce the efficiency of the financial market; (ii) a good case can be made for elevating the role of the misalignment of asset prices (including exchange rates) and financial imbalances in the conduct of monetary policy; and (iii) financial stability should take on greater importance as an objective for public policy. Whether and how much of the financial stability objective should be assigned to the central bank is still an open question.
Keywords: E52; E58; 330; Geldpolitik; Wirkungsanalyse; Asiatisch-pazifischer Raum